Improvement of the military academy education system for aeronautics students using the flying laboratory - Stupar, Slobodan N.; Simonović, Aleksandar M.; Filipović, Zoran Lj.; Jovanović, Miroslav Miodrag (Vojnotehnički glasnik / Military Technical Courier, 2013)
This paper describes a proposal to improve the educational process of students of the Military Academy to support the maintenance process of the Serbian Army aircraft based on the introduction of objects in flight test aircraft. It is particularly emphasized the importance of establishing airline laboratories with basic characteristics of the test-measuring equipment that is necessary to integrate the aircraft to perform a practical test of an aircraft in flight. The formation of aircraft laboratories would form a very strong didactic tool, which provides for optimal synthesis of theory and practice. This concept of improving the educational process would be substantially affected the awareness of the necessity of working together and put together all the research capacity of scientific institutions in the Ministry of Defence of the Republic of Serbia.